BIOGENIC GAS IN DELTAIC DEPOSITION ENVIRONMENT IN KAPUAS RIVER, WEST KALIMANTAN AND ITS UTILIZATIONS FOR LOCAL COMMUNITY - Hananto Kurnio; Yudi Darlan (Marine Geological Institute of Indonesia, 2009)
Biogenic gas within a deltaic deposition environment in the Kapuas rivermouth of West Kalimantan occurred in fine to very fine quartz sand reservoir of shallow boreholes of having the depth of 1-12 m below ground surface. This reservoir is covered by peaty layers of semi-impermeable property. During high tide, gas bubbling took place in the water column above the ground of these semi-impermeable layers. Utilizations of biogenic gas had been done succesfully. These works were carried out through drilling, piping, gas storage and installations for gas stove and gas electricity generator of 500 watt capacity at chief village house as an example before widely used to the local community. Keywords: Biogenic Gas; Deltaic Deposition Environment; Kapuas River; west Kalimantan, Utilization. Gas biogenik dalam suatu lingkungan pengendapan delta di muara Sungai Kapuas Kalimantan Barat terdapat dalam reservoar pasir kuarsa berukuran halus hingga sangat halus pada kedalaman bor dangkal 1-12 m di bawah permukaan tanah. Reservoar ini ditutupi oleh lapisan gambut semiimpermeabel. Selama pasang naik, gelembung gas teramati dalam kolom air di atas permukaan lapisan semi-impermeabel ini. Pemanfaatan gas biogenik telah dilaksanakan dengan sukses. Pemanfaatan ini dilakukan melalui pemboran, pipanisasi, penampungan gas dan instalasi untuk kompor gas dan generator listrik berbahan bakar gas kapasitas 500 watt di rumah Kepala Desa sebagai contoh sebelum dimanfaatkan secara luas oleh masyarakat setempat. Kata kunci: Gas Biogenik, Lingkungan Pengendapan Delta, Sungai Kapuas, Kalimantan Barat, Pemanfaatan